Modern lifestyle, Non Veg Food and Its Impact on Environmental Aspects (Global Journal of Human-Social Science, 2012)
Background Human s life style has changed dramatically over the time The consumption of meat and meat production has increased radically through out the world Global demand for food is expected to increase by 70 by 2050 FAO 2009 This excessive growth in meat production consumption brings several impacts on environmental resources The paper discusses change in people s lifestyle and consumption pattern of non veg food all over the world The consequences of meat production live stock farming on water land use rain forest and climate change are discussed Materials and methods Data from U S Department of Agriculture Foreign Agriculture Service 2010 is used for meat consumption analysis Global data of 1965-2005 obtained from the U N Food and Agricultural Organization FAOSTAT livestock database is used for projection
Keywords: Meat Consumption; Environmental Impacts; Modern life style; Non veg food; Climate change